Chromium(II) Alkylcyclopentadienyl Complexes with Carbon or Hydride Donor Ligands - Smytschkow, Igor; Gidt, Wjatscheslaw; Sun, Yu; Langer, Jens; Boettcher, Tobias; Kubickova, Lenka; Kaman, Ondrej; Sitzmann, Helmut (Organometallics, 2021)
Alkylcyclopentadienylchromium(II) bromide dimers [Cp‴Cr(μ-Br)]2 and [5CpCr(μ-Br)]2 (Cp‴ = tri(tert-butyl)cyclopentadienide, 5Cp = pentaisopropylcyclopentadienide) have been used as starting compounds for replacement of bromide with methyl, hydride, phenyl, phenylacetylide, cyanide, or tetrahydroaluminate anions and afforded dinuclear chromium(II) complexes except for cyanide and tetrahydroaluminate, where tetranuclear products were isolated. Mononuclear chromium complexes have been synthesized by N-heterocyclic carbene addition to the bromide complex or by bromide substitution with a cyclopentadienyl or another alkylcyclopentadienyl ligand. Strong antiferromagnetic coupling with J1,2 = -206 cm-1 of two high-spin Cr(II) central atoms has been found for the dinuclear hydride [Cp‴Cr(μ-H)]2, which was obtained during reactions with isopropylmagnesium chloride via β-hydride elimination and was also found after attempted potassium reduction of the chromium(II) starting compound. Diamagnetic behavior was observed only for the tetranuclear aluminumtetrahydro-tri(tert-butyl)chromate(II).
CRIS-Team Scopus Importer:2021-09-24